Exploring the epoch of hydrogen reionization using FRBs. Issue 4 (4th February 2021) - Beniamini, Paz; Kumar, Pawan; Ma, Xiangcheng; Quataert, Eliot
ABSTRACT: We describe three different methods for exploring the hydrogen reionization epoch using fast radio bursts (FRBs) and provide arguments for the existence of FRBs at high redshift ( z ). The simplest way, observationally, is to determine the maximum dispersion measure (DMmax ) of FRBs for an ensemble that includes bursts during the reionization. The DMmax provides information regarding reionization much like the optical depth of the cosmic microwave background to Thomson scattering does, and it has the potential to be more accurate than constraints from Planck, if DMmax can be measured to a precision better than 500 pccm −3 . Another method is to measure redshifts of about 40 FRBs between z of 6 and 10 with 10 per cent accuracy to obtain the average electron density in four different z -bins with 4 per cent accuracy. These two methods do not require knowledge of the FRB luminosity function and its possible redshift evolution. Finally, we show that the reionization history is reflected in the number of FRBs per unit DM, given a fluence limited survey of FRBs that includes bursts during the reionization epoch; we show using FIRE simulations that the contribution to DM from the FRB host galaxy and circumgalactic medium during the reionization era is a small fraction of the observed DM. This third method requires no redshift information but does require knowledge of the FRB luminosity function.